Structural Materials Based on Polyolefins - Rosilov Mansur Sirgiyevich; Jo’rayev Elbek Sirgi o’g’li (Research Parks Publishing LLC, 2022)
Antifriction and antifriction-wear-resistant composite polymer materials. The friction of raw cotton with a composite material has a complex nature. The mechanism of interaction of these bodies during friction is influenced by both molecular and mechanical processes.